Women's community organizations: Exploring attitudes toward collaboration among board members. Issue 1 (1st January 2017) - Cumberland, Denise M.; Kerrick, Sharon A.; Choi, Namok; Gosser, Kathleen
Abstract: There has been tremendous growth of women's community organizations over the past 40 years. The aims and efforts for these organizations range from educational, financial, medical, and human services, to career and professional development. While the span of interests and causes varies, the commonality these groups share is the quest to have positive impact on the lives of women in local communities. This study assesses types and levels of collaboration occurring among women's community organizations in a midwestern city in the US. The Theory of Reasoned Action is used to explain attitudes about knowledge sharing and collaboration. Results reveal that there is a link between a positive attitude toward collaboration and an intention to share knowledge. Furthermore, factors such as perception of reciprocity and perception of low barriers to collaboration are significantly associated with knowledge sharing attitudes.